2020
DOI: 10.1177/0300060520966458
|View full text |Cite
|
Sign up to set email alerts
|

Mental health research in Botswana: a semi-systematic scoping review

Abstract: Mental and substance use disorders are a leading cause of disability worldwide. Despite this, there is a paucity of mental health research in low- and middle-income countries, especially in sub-Saharan Africa. We carried out a semi-systematic scoping review to determine the extent of mental health research in Botswana. Using a predetermined search strategy, we searched the databases Web of Science, PubMed, and EBSCOhost (Academic Search Complete, CINAHL with Full Text, MEDLINE, MEDLINE with Full Text, MLA Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…There was a spike in suicidal behavior and depression rates among young people in Botswana in 2021, as shown by the unpublished hospital record in Botswana's only mental health referral hospital. Studies on depression focused mainly on university students [9][10][11][12] and adults in community settings [9][10][11]. The few studies conducted among individuals living with HIV were mainly in the adult population [13][14][15][16] and conducted more than 10 years ago [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a spike in suicidal behavior and depression rates among young people in Botswana in 2021, as shown by the unpublished hospital record in Botswana's only mental health referral hospital. Studies on depression focused mainly on university students [9][10][11][12] and adults in community settings [9][10][11]. The few studies conducted among individuals living with HIV were mainly in the adult population [13][14][15][16] and conducted more than 10 years ago [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The few studies conducted among individuals living with HIV were mainly in the adult population [13][14][15][16] and conducted more than 10 years ago [13,14]. At the time of writing, no study was found that estimated the prevalence of depression among the ALWHIV in Botswana, which ranked among the top four countries most affected by HIV [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although the country has relatively high number of HCWs per capita compared with others in the region, these are inadequate and unevenly distributed. 17 , 18 The country recorded its first cases of COVID-19 in March 2020, and since then, the cases have been rising. At the time of writing, there were 46,934 cases reported, with 712 deaths (Coronavirus Resource Center, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to two recent scoping reviews conducted in South Africa and Botswana, more research work has been done on substance use in Kenya. Our study found that 185 papers on substance use among Kenyans had been published by the time of the search while Opondo et al[11] and Tran et al[10] reported that only 53 and 7 papers focusing on substance use had been published in South Africa (between 1971 and 2017) and in Botswana (between 1983 and 2020) respectively.…”
mentioning
confidence: 57%
“…In another survey, 20% of primary school children had ever used at least one substance in their lifetime [9]. Moreover, Kenya has the third highest total DALYs (54,000) from alcohol use disorders (AUD) in Africa [4] Unfortunately, empirical work on substance use in LMICs is limited [10,11]. In a global mapping of SUD research, majority of the work had been conducted in upper-middle income and HICs (HICs) [11].…”
Section: Introductionmentioning
confidence: 99%